1996
DOI: 10.1080/07929978.1996.10676652
|View full text |Cite
|
Sign up to set email alerts
|

The Barbaloin Content and Distribution in Aloe Arborescens Leaves According to the Leaf Part, Age, Position, and Season

Abstract: The distribution of the secondary phenolic compound, barbaloin, in Aloe arborescens leaves depends on the leaf part, age, and position of the leaf, as well as on seasonal influences. Young and old leaves of A. arborescens were cut from plants monthly and the exudate was immediately freeze-dried. The barbaloin levels were determined spectrophotometrically at λmax, 360–362 nm after separation by TLC. In all leaves the tissue of the basal third of the leaf had the lowest barbaloin content, the upper third contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…In previous studies it was found that in different Aloe species the barbaloin or homonataloin content was higher in younger than in older leaves (Birch & Donavan 1955;Takayulu & Toshifiumi, 1983;Nakagomi et al, 1985;Groom & Reynolds, 1987;Yamamoto et al, 1991;Chauser-Volfson & Gutterman, 1996, 1998. It has also been found that the terminal third of the leaves have the highest percentages of these secondary metabolites and the leaf base third, the lowest (Chauser-Volfson & Gutterman, 1996& Gutterman, , 1997& Gutterman, , 1998.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In previous studies it was found that in different Aloe species the barbaloin or homonataloin content was higher in younger than in older leaves (Birch & Donavan 1955;Takayulu & Toshifiumi, 1983;Nakagomi et al, 1985;Groom & Reynolds, 1987;Yamamoto et al, 1991;Chauser-Volfson & Gutterman, 1996, 1998. It has also been found that the terminal third of the leaves have the highest percentages of these secondary metabolites and the leaf base third, the lowest (Chauser-Volfson & Gutterman, 1996& Gutterman, , 1997& Gutterman, , 1998.…”
Section: Discussionmentioning
confidence: 82%
“…It has also been found that the terminal third of the leaves have the highest percentages of these secondary metabolites and the leaf base third, the lowest (Chauser-Volfson & Gutterman, 1996& Gutterman, , 1997& Gutterman, , 1998.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…3. Squeezing the leaf tissues and freeze drying the exudates in order to separate the SPhMs from the exudates (since 1996 we as well as others have used this method in all our research) [3,5,13,15]. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Its highest in the terminal third of the leaf, at its lowest in the basal third; higher in the terminal, adaxial, leaf margin and lower in the basal, abaxial, leaf centre [1] . The distribution of barbaloin, in Aloe arborescens leaves was shown to depend on the leaf part, age, and position of the leaf, as well as on seasonal influences [17] . Plants that are subjected to repeated leaf pruning respond by increasing the content of their secondary phenol metabolites (SPhMs).…”
Section: Effect Of Seasonal Variation On Barbaloin Contentmentioning
confidence: 96%